RELATIONSHIP BETWEEN VISUAL INSPECTION WITH ACETIC ACID POSITIVITY AND CERVICAL INTRAEPITHELIAL NEOPLASIA DIAGNOSIS AMONG WOMEN IN ZIMBABWE: A RETROSPECTIVE STUDY - Chipenzi, Tanyaradzwa; Salissou, Maibouge Tanko Mahamane (Journal of Public Health Research and Community Health Development, 2025)
Background: The burden of cervical cancer (CC) in Zimbabwe amount   to 19%.  Early detection is essential tools in fight against CC. Visual Inspection with Acetic Acid (VIAC) and Loop Electrosurgical Excision Procedure (LEEP) were commons screening tools for CC in Zimbabwe however their sensitivity and specificity are still questionable. At Cimas medical laboratory an increasing number of VIAC positivity was reported in recent years. Purpose: We tested if VIAC positivity can be a predictor of CIN (cervical intraepithelial neoplasia) diagnosis using LEEP histological analysis. Methods: A retrospective study was conducted, for women aged 16-70 who underwent VIAC and LEEP histological analysis. CIN diagnosis was based on LEEP histological analysis findings. A chi-square test was used to determine the relationship between VIAC positivity and CIN diagnosis. 372 participants were included using stratified sampling. Results: Incidence of CIN diagnosis was 61.8%. Age group 38 to 48 showed the highest number of High Grade Cervical Intra Epithelial Lesion (HSIL) of 78(34%) and Low Grade Cervical Intra Epithelial Lesion (LSIL) of 30(13%). According to geographic location the highest number of CIN cases were observed in Gweru with 86 cases. A sensitivity of 88.1%, specificity of 93.8%, Negative Predictive Value of 100%and Positive predictive value of 96.64% were observed. Human Immunodeficiency Virus (HIV) was the main risk factor in CIN and VIAC positive individuals. Conclusion: The incidence of CIN was higher than National rate; with HIV as major risk factors. There was a positive relationship between VIAC positivity and CIN diagnosis using LEEP histological analysis.